2015
DOI: 10.1111/ddg.12510
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for diagnosis, prevention and treatment of hand eczema – short version

Abstract: The guidelines aim to provide advice on the management of hand eczema (HE), using an evidence- and consensus-based approach. The guidelines consider a systematic Cochrane review on interventions for HE, which is based on a systematic search of the published literature (including hand-searching). In addition to the evidence- and consensus-based recommendation on the treatment of HE, the guidelines cover mainly consensus-based diagnostic aspects and preventive measures (primary and secondary prevention). Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 114 publications
(147 reference statements)
1
60
1
11
Order By: Relevance
“…Considering their long history of use, it seems odd that the recent Cochrane review identified only nine studies that evaluated topical corticosteroids as the main intervention. 6 For long-term use, topical glucocorticosteroids with an improved therapeutic index (TIX, ratio between desired effects and especially atrophogenic side effects) should be considered. 4 The present ESCD guidelines recommend topical corticosteroids as first-line treatment in the management of hand eczema, but they point to the fact that as they may be very effective in the short term, they may inhibit epidermal barrier repair and cause skin atrophy, thus interfering with recovery in the long term.…”
Section: Topical Glucocorticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering their long history of use, it seems odd that the recent Cochrane review identified only nine studies that evaluated topical corticosteroids as the main intervention. 6 For long-term use, topical glucocorticosteroids with an improved therapeutic index (TIX, ratio between desired effects and especially atrophogenic side effects) should be considered. 4 The present ESCD guidelines recommend topical corticosteroids as first-line treatment in the management of hand eczema, but they point to the fact that as they may be very effective in the short term, they may inhibit epidermal barrier repair and cause skin atrophy, thus interfering with recovery in the long term.…”
Section: Topical Glucocorticosteroidsmentioning
confidence: 99%
“…37 Also in a sequential maintenance therapy study of atopic hand eczema, pimecrolimus 1% cream twice daily was not superior to vehicle. 6 The most valuable advantage of the compounds is their safety over longterm usage, without the induction of atrophy or interference with barrier repair. 6 The most valuable advantage of the compounds is their safety over longterm usage, without the induction of atrophy or interference with barrier repair.…”
Section: Topical Immune Modulatorsmentioning
confidence: 99%
“…Symptoms of hand eczema (HE)/dermatitis include erythema, dryness, fissures, itching, vesicles, papules and hyperkeratosis; the most frequently affected areas are the backs of the hands and fingers (2)(3)(4)(5). Chronic HE (CHE) is defined as eczema that persists for >3 months or recurs !2 times within 12 months, despite sufficient therapy and appropriate patient adherence (3). Epidemiologic data on CHE in the United States are sparse; one survey of self-reported CHE in a managed care organization estimated the prevalence to be 16% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Management of sCHE is difficult, with few available treatments for patients who become refractory to potent topical corticosteroids (2,3,5,13,18,19). In the United States, there are no agents specifically indicated for treatment of sCHE refractory to potent topical corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…Am Anfang und im Vordergrund stehen stets die ambulante dermatologische Diagnostik und Therapie, für deren Qualitätssicherung im Patientenmanagement mittlerweile eine S3-Leitlinie existiert [7]. Ambulante Leistungen umfassen das Angebot von Hautschutzschulungsmaßnahmen, zumeist in Form eines sog.…”
unclassified